The Effect of Customer Satisfaction on the Service at Lady Salon during the Covid-19 Pandemic - Rieneke R. Kalalo; Jane Elvira Scipio; Jola Silvana Kalangi; lenda Lumentah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The impact of Coronavirus (Covid-19) pandemic is strongly affected in business and economic world. A fairly short time path to marketing patterns changes especially when treated with Large-Scale Social Restrictions. Marketing products or services to consumers as a brand strategy survive in the Covid-19 pandemic. This study aimed to analyze the influence of Lady Salon’s customer satisfaction during the Covid-19 Pandemic. Quantitative analysis methods were based on causal analysis designs in which the data was processed by linear regression analysis. The results of the study stated that the service of the beauty salon business significantly affected the customer satisfaction at Lady Salon in Kamasi Village and the relationship between its service and its customer satisfaction. This was also supported by the achievement rate of descriptive test respondents on service variables included in the highest average value that answered the most agreed questions which means that the respondents were very satisfied with the products available at Lady Salon and trusted. As for the customer satisfaction variables included in the highest average scores that answered the most agreed questions which means that the respondents were satisfied with its appropriate service to its customers. Therefore, it can be concluded that Lady Salon needs to increase customer satisfaction in the terms of handling complaints, and the company services are supposed to continue improving.